Pembagian Harta Bersama Dalam Perceraian Suku Batak Toba Yang Menganut Kepercayaan Parmalim - Verlyta Swislyn; Udin Narsudin; Nurwidiatmo N (Jurnal Nuansa Kenotariatan, 2018)
In the Batak Toba tribe which impressed traditional, it has stronger and more strict rules of customs in terms of the distribution of shared assets. Before the emergence of Batak Toba which embraced Christianity, the belief of Parmalim, Parmalim was a spiritual movement to maintain ancient customs and beliefs that were threatened due to the new religion brought by the Dutch. The Batak Toba have a very strong regulation in terms of divorce, almost in Batak Toba households do not know of divorce, but when there is a divorce in the Batak Toba tribe that still adheres to the belief of Parmalim, it is very interesting to study further about the marriage carried out in customs until the divorce was carried out in accordance with the rules of the Batak Toba customs which had the trust of Parmalim up to the distribution of joint assets carried out in a customary manner. The method used in this study is normative juridical supported by empirical jurisdiction. The results of the research, it can be obtained how the sharing of joint assets due to divorce in the Batak Toba tribe which adheres to the belief of Parmalim, disputes regarding joint assets, the resolution of disputes through the customary elders deliberation and the results of deliberation are the applicable laws, as well as factors faced in the distribution of together assets there are internal and external factors